Development of high temperature nanoindentation methodology and its application in the nanoindentation of polycrystalline tungsten in vacuum to 950 ºC - Harris, A; Beake, B; Armstrong, D; Davies, M (Springer US, 2016)
The capability for high temperature nanoindentation measurements to 950 ºC in high vacuum has been demonstrated on polycrystalline tungsten, a material of great importance for nuclear fusion and spallation applications and as a potential high temperature nanomechanics reference sample. It was possible to produce measurements with minimal thermal drift (typically ~0.05 nm/s at 750-950 ºC) and no visible oxidative damage. The temperature dependence of the hardness, elastic modulus, plasticity index, creep, creep strain, and creep recovery were investigated over the temperature range, testing at 25, 750, 800, 850, 900 and 950 ºC. The nanoindentation hardness measurements were found to be consistent with previous determinations by hot microhardness. Above 800 ºC the hardness changes relatively little but more pronounced time-dependent deformation and plasticity were observed from 850 ºC. Plasticity index, indentation creep and creep recovery all increase with temperature. The importance of increased time-dependent deformation and pile-up on the accuracy of the elastic modulus measurements are discussed. Elastic modulus measurements determined from elastic analysis of the unloading curves at 750-800 ºC are close to literature bulk values (to within ~11%). The high temperature modulus measurements deviate more from bulk values determined taking account of the high temperature properties of the indenter material at the point (850 ºC) at which more significant time-dependent deformation is observed. This is thought to be due to the dual influence of increased time-dependency and pile-up that are not being accounted for in the elastic unloading analysis. Accounting for this time-dependency by applying a viscoelastic compliance correction developed by G. Feng and A.H.W. Ngan (J. Mater. Res. (2002) 17:660-668) greatly reduces the values of the elastic modulus, so they are agree to within 6% of literature values at 950 ºC.